Silencing of the insulin receptor isoform A favors formation of type 1 insulin-like growth factor receptor (IGF-IR) homodimers and enhances ligand-induced IGF-IR activation and viability of human colon carcinoma cells. - Brierley, G; Macaulay, S; Forbes, B; Wallace, J; Cosgrove, L; Macaulay, V (2010)
Insulin receptor (IR) overexpression is common in cancers, with expression of the A isoform (IR-A, exon 11-) predominating over the B isoform. The IR-A signals a proliferative, antiapoptotic response to IGF-II, which itself can be secreted by tumors to establish an autocrine proliferative loop. Therefore, IGF-II signaling via the IR-A could mediate resistance to type 1 IGF receptor (IGF-IR) inhibitory drugs that are currently in development. This study addressed the role of the IR-A, using a small interfering RNA-based approach in SW480 human colon adenocarcinoma cells that coexpress the IGF-IR. Clonogenic survival was inhibited by depletion of the IGF-IR but not the IR-A, and dual receptor depletion had no greater effect than IGF-IR knockdown alone, suggesting that the IR-A could not compensate for IGF-IR loss. IGF-IR knockdown also resulted in a decrease in viability, whereas IR-A depletion resulted in increased viability. Consistent with this, upon IR-A depletion, we found a concomitant enhancement of IGF-IR activation by IGF-I and IGF-II, reduced formation of IGF-IR:IR-A hybrid receptors and increased IGF-IR homodimer formation. Together, these results suggest that IGF bioactivity is mediated more effectively by the IGF-IR than by the IR-A or receptor hybrids and that signaling via the IGF-IR is dominant to the IR-A in colon cancer cells that express both receptors.